Estimation of Earthquake Intensity and Peak Ground Acceleration in West Java Using the MC Guire and the Lin & Lee Method - Resi Silvianis; Syafriani; Letmi Dwiridal; Zulhendra (Kappa Journal, 2024)
Abstract:  West Java province was in a subduction zone and fault zone (slip fault), which caused earthquakes. Therefore, it was necessary to research estimates of maximum ground acceleration in West Java to mitigate earthquake disasters. This research also aimed to determine the value of ground acceleration and earthquake intensity and to determine the distribution map using the McGuire method and the Lin & Lee method. The data used were earthquake data for 1950-2023 with a magnitude > 5 SR. From processing this data, the maximum ground acceleration value in West Java ranged between 10.14722-195.3540 gal, and the maximum intensity value was IV-VI MMI using the Mc Guire method. Meanwhile, for the Lin & Lee method, it ranged between 6.6512 to 49.24599 gal. Of the two methods, the largest maximum ground acceleration value was located in Cianjur Regency, which was due to its proximity to the Cimandiri fault and the geological conditions in the area.